Aliran Rasionalisme dan Empirisme dalam Kerangka Ilmu Pengetahuan - Susanti Vera; R. Yuli A. Hambali (Jurnal Penelitian Ilmu Ushuluddin, 2021)
This study aims to discuss the flow of rationalism and empiricism within the framework of science. The research method used is a qualitative type through literature study. The result and discussion of this research is that there are fundamental differences between science and knowledge at the level of philosophy of science. Science and knowledge are produced by human absorption of everything that is guided by curiosity (curiosity) which is human nature. The knowledge that is owned is then tested for accuracy by fulfilling three basic aspects of science, namely ontology (the object of knowledge), epistemology (how to obtain knowledge), and axiology (the use value of science). This study concludes that epistemologically, there are two understandings about the source of knowledge, namely, rationalism and empiricism. Rationalism believes that reason is the main source of knowledge and emepiriism believes that only sensory experience brings true knowledge. Both of them have a big role in the development of science to reach a critical human civilization and are able to survive as a superior identity in this universe.